JUDAIZM I EKONOMIA. ZWIĄZEK JUDAIZMU Z ŻYCIEM GOSPODARCZYM - Fel, Stanisław; Zdun, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article deals with the relationship of Judaism to economic activity. The subject is the typical approach of Jewish ethical thought, concerning the understanding of money, wealth, jobs and economic initiatives. Issues related to fundamental economic life are shown to be covered in the books that the Jewish community considers sacred. Particularly important are the Old Testament and the Talmud. Also important are references to the cultural interpretation of Judaism, including the classical works on the subject – Jacques Attali and Werner Sombart. The key concept is the subject of “wealth,” the meaning of which is derived from the Bible’s Book of Exodus and the Talmud. Finally, the foundations for Jewish economic thought can be expressed as the product of an embedded culture, which is founded on religion, in which property acquires ethical legitimacy. The argument is crowned with historical examples of the noble economic activity of the Jewish people, which also give evidence of the interrelatedness of religion and the proper use of wealth.